(untitled) (Mustansiria Dental Journal, 2018)
Background: oroantral communication (OAC) is abnormal connection between oral cavity and maxillary sinus. OAC is a rare, well known complication, mostly occurs after the extraction of upper posterior teeth, and if not treated lead to formation of oroantral fistula (OAF) and many complications .surgical repair is very necessary to prevent further complications .The aim of this study to evaluate and analyze the clinical, radiographic aspects of 39 Iraqi patients with oroantral fistula. Materials and methods :the study was carried on 39 patients with oroantral fistula reported to the Department of oral and maxillofacial surgery ,college of dentistry, University of Baghdad ,and private practice from 1983 to 2010 .data regarding the age ,sex , cause ,site ,radiographic features and types of radiographs ,signs and symptoms ,duration ,relation to the adjacent teeth , sinus disease ,methods of treatment . Results: 39 cases of OACs, 26 male, 13 female, the age range was20-65 with a mean age 44.5 year. Highest incidence was seen in the third and fourth decade of life 61.4%. The highest frequency of OACs was seen in relation to upper first molar 48.7% .the commonest cause was complicated extraction 51.2% .pain and tenderness was the most prominent symptoms 80%, escape of fluid from the nose was the most prominent sign 75.6%.there was a long delay in the diagnosis and treatment .most of the OACs occurs near the edentulous areas, occipitomental radiograph was not reliable in detection of displaced roots. Buccal advancement flap was the main method in treatment 81.2%. Conclusions: OACs a rare complication, its management need good clinical and radiological experience, and the treatment should be individualized to have good results.